2009
DOI: 10.1111/j.1468-3148.2009.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Majority and Minority Ethnic Family Carers of Adults with Intellectual Disabilities: Perceptions of Challenging Behaviour and Family Impact

Abstract: Background A health service in an English city was concerned about its support to families with adults with intellectual disabilities and challenging behaviour. Methods Semi-structured interviews were conducted with seven minority ethnic and seven majority ethnic family members to explore perceptions of challenging behaviour, support and the impact of the person on the family. These were analysed using interpretative phenomenological analysis. Results Four themes emerged: (i) A broad range of difficulties with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Interestingly, the parents described getting a diagnosis and seeking medical help early on. This emphasis on early intervention and diagnosis is very distinct from other research in which South Asian parents often have low service uptake and receive later diagnoses of disabilities (Bywaters et al, 2003;Hatton et al, 2010). This may be influenced by the fact that the parents in the current study demonstrated higher levels of integration with British culture.…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, the parents described getting a diagnosis and seeking medical help early on. This emphasis on early intervention and diagnosis is very distinct from other research in which South Asian parents often have low service uptake and receive later diagnoses of disabilities (Bywaters et al, 2003;Hatton et al, 2010). This may be influenced by the fact that the parents in the current study demonstrated higher levels of integration with British culture.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies have found that parents and individuals with I/DD considered service accessibility, availability, flexibility of family‐focused services and staff who allow families and individuals with I/DD to maintain their independence as much as possible to be important (Barelds, van de Goor, Bos, van Heck, & Schols, ; Bigby, ; Caldwell & Heller, ; Gallivan‐Fenlon, ; Herman, Marcenko, & Hazel, ; Knox & Bigby, ; Freedman & Boyer, ; Rourke, Grey, Fuller, & Mcclean, ; Weller, ). Qualified, empathetic and culturally sensitive staff have also been identified as factors influencing satisfaction with services (Barelds, van de Goor, van Heck & Schols, , Grant, McGrath, & Ramcharan, ; Hatton et al., ; Hatton et al., ; Larsson & Larsson, ; Rourke et al., ; Shapiro, Monzo, Rueda, Gomez, & Blacher, ).…”
Section: Resultsmentioning
confidence: 99%
“…Many South Asian communities face inequality in housing, employment and economic disadvantage. Higher levels of unemployment, lack of benefits and racism also adds greater psychological stress to these families (see Hatton et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
“…2001). Higher rates of psychological distress among South Asian carers of children with ID have been found (Hatton et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation